The supplementation of the multi-strain probiotics WHHPRO™ alleviates high-fat diet-induced metabolic symptoms in rats via gut-liver axis - Chen, Cailing; Gao, Kan; Chen, Zuoguo; Zhang, Qiwen; Ke, Xueqin; Mao, Bingyong; Fan, Qiuling; Li, Yanjun; Chen, Su (Frontiers in Nutrition, 2024)
Metabolic syndrome (MS) has emerged as one of the major global health concerns, accompanied by a series of related complications, such as obesity and type-2 diabetes. The gut-liver axis (GLA) is a bidirectional communication between the gut and the liver. The GLA alterations have been revealed to be closely associated with the development of MS. Probiotics within Lactobacillus and Bifidobacterium confer beneficial effects on improving MS symptoms. WHHPRO™ is a mixture of four probiotic strains, with potential MS-improving abilities. This study aimed to investigate the effects of WHHPRO™ on MS symptoms using a high-fat diet (HFD) rat model. Oral administration of WHHPRO™ for 12 weeks improved glucose tolerance, blood lipid, body weight, and liver index in HFD rats. WHHPRO™ shaped the gut microbiome composition by increasing the abundance of Lactobacillus and Akkermansia and normalized the reduced SCFA levels in HFD rats. Besides, WHHPRO™ modulated the fecal bile acids (BAs) profile, with decreased levels of T-b-MCA and 12-KDCA and increased levels of LCA and ILCA. Meanwhile, WHHPRO™ increased total unconjugated BAs in feces and liver and reduced the accumulation of total hepatic BA pool size in HFD rats. Moreover, WHHPRO™ reversed the expression of genes associated with impaired BA metabolism signaling in the ileum and liver. Our findings suggest that WHHPRO™ exerted beneficial effects on improving MS symptoms, involving the modulation of the gut microbiome composition, SCFAs, and the FXR-FGF15 signaling along the GLA. Supplementation of WHHPRO™ may serve as a novel strategy for improving MS symptoms.